2015
DOI: 10.1021/acs.jpcc.5b03285
|View full text |Cite
|
Sign up to set email alerts
|

Some Quinoxalin-6-yl Derivatives as Corrosion Inhibitors for Mild Steel in Hydrochloric Acid: Experimental and Theoretical Studies

Abstract: The inhibition of mild steel corrosion in 1 M HCl by some quinoxalin-6-yl derivatives namely 1-[3-phenyl-5-quinoxalin-6-yl-4,5-dihydropyrazol-1-yl]­butan-1-one (PQDPB), 1-(3-phenyl-5-(quinoxalin-6-yl)-4,5-dihydro-1H-pyrazol-1-yl)­propan-1-one (PQDPP), and 2-phenyl-1-[3-phenyl-5-(quinoxalin-6-yl)-4,5-dihydropyrazol-1-yl]­ethanone (PPQDPE) has been investigated using electrochemical studies and quantum chemical calculations. The results showed that PQDPP is the best corrosion inhibitor among the three compounds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
137
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 420 publications
(149 citation statements)
references
References 63 publications
10
137
0
2
Order By: Relevance
“…This implies that the inhibitors reduce the corrosion current densities at the Al/electrolyte interface thereby reduce the rate of Al corrosion in 1 M HCl. The shapes of the polarization curves for the blank and inhibitor-containing electrochemical systems are similar, which suggests that the inhibitors retard Al corrosion in 1 M HCl by blocking the active sites on the Al surface without altering the mechanism of the corrosion reaction [9]. Electrochemical corrosion parameters such as corrosion potential (Ecorr), corrosion current density (icorr), anodic and cathodic Tafel slopes (ba and bc respectively) were obtained by the extrapolation of the Tafel regions of the polarization curves to the Ecorr.…”
Section: Potentiodynamic Polarization Measurementsmentioning
confidence: 81%
See 2 more Smart Citations
“…This implies that the inhibitors reduce the corrosion current densities at the Al/electrolyte interface thereby reduce the rate of Al corrosion in 1 M HCl. The shapes of the polarization curves for the blank and inhibitor-containing electrochemical systems are similar, which suggests that the inhibitors retard Al corrosion in 1 M HCl by blocking the active sites on the Al surface without altering the mechanism of the corrosion reaction [9]. Electrochemical corrosion parameters such as corrosion potential (Ecorr), corrosion current density (icorr), anodic and cathodic Tafel slopes (ba and bc respectively) were obtained by the extrapolation of the Tafel regions of the polarization curves to the Ecorr.…”
Section: Potentiodynamic Polarization Measurementsmentioning
confidence: 81%
“…The dissolution of Al has been reported to be more rapid in acidic solutions containing chloride or fluoride ions than in the near-neutral solutions [4][5][6]. Corrosion inhibitors offer an efficient, a convenient and relatively cheap method of controlling corrosion of metals in various aggressive media [3,[7][8][9][10][11]. For this reason, a number of studies have been reported on the use of corrosion inhibitors to mitigate the corrosion of Al in chloride solutions [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SEM principle consists of an electron beam scanning the surface of the sample to be analyzed that, in response, re-emits certain particles. These particles are analyzed by different detectors, which make it possible to reconstruct a three-dimensional image of the surface [62][63][64][65][66][67][68][69]. In order to evaluate the morphology of the surface of the steel to prove whether the inhibition is due to the formation of a film of organic molecules on its surface, we have used scanning electron microscopy (SEM).…”
Section: Characterization Of the Surface Area By Scanning Electron MImentioning
confidence: 99%
“…In recent times, molecular dynamics simulations are commonly used as an efficient tool to evaluate the interaction of corrosion inhibitor and metal surface [3,7,[10][11][12][13][14], which plays a significant role in understanding the corrosion inhibition phenomena. This type of simulation provides more insights into the structure of the interface and how it differs from the bulk and the interaction of inhibitor molecules with metal surface [7,15,16].…”
Section: Introductionmentioning
confidence: 99%